Heat affected zones and oxidation marks in fiber laser-oxygen cutting of mild steel - Al-Mashikhi, S.O.; Powell, J.; Kaplan, A.F.H.; Voisey, K.T. (Laser Institute of America, 2011)
The effect of cutting speed and sheet thickness on surface oxidation and heat affected zones (HAZs) has been investigated for laser-oxygen cutting of mild steel sheet with a fiber laser. Optical and scanning electron micrographs were used to determine the extent of surface oxidation and HAZ from plan and cross-sectional views, respectively. The HAZ is consistently wider at the bottom of the cut compared to the HAZ at the top of the cut. With increasing speed, the width of the HAZ at the top of the cut decreases whereas the HAZ width at the bottom of the cut generally increases. No simple, direct relationship between HAZ width and surface oxidation was seen. However, it is possible to state that in each case considered here, the HAZ would be completely removed if they are machined back by a depth equal to the extent of the surface oxidation. (C) 2011 Laser Institute of America.